The Oncogene Metadherin Interacts with the Known Splicing Proteins YTHDC1, Sam68 and T-STAR and Plays a Novel Role in Alternative mRNA Splicing - Luxton, Hayley J. (Cancers (Basel), 2019)
Oncogenic metadherin is a key contributor to tumourigenesis with metadherin expression and cytoplasmic localisation previously linked to poor survival. A number of reports have shown metadherin localises specifically to nuclear speckles known to be rich in RNA-binding proteins including the splicing proteins YTHDC1, Sam68 and T-STAR, that have been shown to select alternative splice sites in mRNA of tumour-associated proteins including BRCA, MDM2 and VEGF. Here we investigate the interaction and relationship between metadherin and the splice factors YTHDC1, T-STAR and Sam68. Using a yeast two-hybrid assay and immunoprecipitation we show that metadherin interacts with YTHDC1, Sam68 and T-STAR and demonstrate that T-STAR is significantly overexpressed in prostate cancer tissue compared to benign prostate tissue. We also demonstrate that metadherin influences splice site selection in a dose-dependent manner in CD44v5-luc minigene reporter assays. Finally, we demonstrate that prostate cancer patients with higher metadherin expression have greater expression of the CD44v5 exon. CD44v5 expression could be used to discriminate patients with poor outcomes following radical prostatectomy. In this work we show for the first time that metadherin interacts with, and modulates, the function of key components of splicing associated with cancer development and progression.